The Cloakroom Rule of International Reserves: Comment - Grubel, Herbert G. (Quarterly Journal of Economics, 1966)
Journal Article The Cloakroom Rule of International Reserves: Comment Get access Herbert G. Grubel Herbert G. Grubel University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 80, Issue 3, August 1966, Pages 485–487, https://doi.org/10.2307/1880735 Published: 01 August 1966